β-Glucosylceramide From Allergic Mothers Enhances Offspring Responsiveness to Allergen - Walker, Matthew T.; Ferrie, Ryan P.; Hoji, Aki; Schroeder-Carter, Lindsay M.; Cohen, Jacob D.; Schnaar, Ronald L.; Cook-Mills, Joan M. (Frontiers in Allergy, 2021)
In animals and humans, offspring of allergic mothers have increased responsiveness to allergen and the allergen-specificity of the offspring can be different than that of the mother. In our preclinical models, the mother’s allergic responses influence development of the fetus and offspring by elevating numbers of cells in dendritic cell subsets. A major question is the identity of maternal factors of allergic mothers that alter offspring development of responsiveness to allergen. Lipids are altered during allergic responses and lipids are transported to the fetus for growth and formation of fetal membranes. We hypothesized that pro-inflammatory lipids, that are elevated in allergic mothers, are transported to the fetus and regulate fetal immune development. We demonstrate in this report that there was a significant 2-fold increase in β-glucosylceramides (βGlcCer) in allergic mothers, the fetal liver and her offspring. The βGlcCer were transported from mother’s plasma, across the placenta, to the fetus and in breastmilk to the offspring. Administration of βGlcCer to non-allergic mothers was sufficient for offspring responses to allergen. Importantly, maternal administration of a clinically relevant pharmacological inhibitor of βGlcCer synthase returned βGlcCer to normal levels in the allergic mothers and her offspring and blocked the offspring increase in dendritic cell subsets and offspring allergen responsiveness. In summary, allergic mothers had increased βGlcCer that was transported to offspring and mediated increases in offspring DCs and responsiveness to allergen. These data have a significant impact on our understanding of mechanisms for development of allergies in offspring of allergic mothers and have the potential to lead to novel interventions that significantly impact risk for allergic disease early in life.